Assessment of the Attitude of The Citizens of The Czech Republic to The Development of Czech-Chinese Trade Relations - David KRIZEK; Kamila VESELA (Communications of International Proceedings, 2021)
The questionnaire method was used to collect information on the attitude of Czech citizens towards trade relations with China, their perception of the quality of Chinese products and the Czech Republic's involvement in the One Belt, One Road project. Based on the responses, null and alternative hypotheses were established and then statistically tested. In general, a rather sceptical attitude prevails in all three areas. However, differences resulting from the age structure of the respondents were identified. A greater degree of scepticism is found among the older generation. The younger generation also perceives the positives arising from mutual trade.
Keywords: Balance of Payments; Export; Foreign Trade; International Relations; Import.